Mexican ballads, Chicano poems : history and influence in Mexican-American social poetry - Limón, José Eduardo (Berkeley : University of California Press, 1992)
Mexican Ballads, Chicano Poems combines literary theory with the personal engagement of a prominent Chicano scholar. Recalling his experiences as a student in Texas, José Limón examines the politically motivated Chicano poetry of the 60s and 70s. He bases his analyses on Harold Bloom's theories of literary influence but takes Bloom into the socio-political realm. Limón shows how Chicano poetry is nourished by the oral tradition of the Mexican corrido, or master ballad, which was a vital part of artistic and political life along the Mexican-U.S. border from 1890 to 1930.Limón's use of Bloom, as well as of Marxist critics Raymond Williams and Fredric Jameson, brings Chicano literature into the arena of contemporary literary theory. By focusing on an important but little-studied poetic tradition, his book challenges our ideas of the American canon and extends the reach of Hispanists and folklorists as well.
pt. 1. Politics, Poetics, and the Residual Precursors, 1848-1958. 1. Borders, Bullets, and Ballads: The Social Making of a Master Poem. 2. Américo Paredes, Tradition, and the First Ephebe: A Poetic Meditation on the Epic Corrido. 3. With His Pistol in His Hand: The Essay as Strong Sociological Poem -- pt. 2. Social Conflict, Emergent Poetry, and the New Ephebes. 4. Chicano Poetry and Politics: The Later Recognition of the Precursor. 5. My Old Man's Ballad: José Montoya and the Power Beyond. 6. The Daemonizing Epic: Rodolfo "Corky" Gonzales and the Poetics of Chicano Rebellion. 7. Juan Gómez-Quiñones: The Historian in the Poet and the Poetic Form of Androgyny -- App A. Harold Bloom: An Exposition and Left Critique -- App B. Juan Gomez-Quinones, "Canto al Trabajador" -- App C. Juan Gómez-Quiñones, "The Ballad of Billy Rivera.
Includes bibliographical references (pages 201-213) and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: American poetry -- Mexican American authors -- History and criticism; Ballads, Spanish -- Appreciation -- Mexico -- United States; Mexican Americans -- Intellectual life; American poetry -- Mexican influences; Mexican Americans in literature; Social problems in literature; Poésie américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique; Américains d'origine mexicaine -- Vie intellectuelle; Poésie américaine -- Influence mexicaine; Américains d'origine mexicaine dans la littérature.; Problèmes sociaux dans la littérature.; Poesía estadounidense -- Autores mexicano-americanos -- Historia y crítica.; Baladas en español -- México -- Apreciación -- Estados Unidos; Mexicano-americanos -- Vida intelectual; Poesía estadounidense -- Influencias mexicanas; Mexicano-americanos en la literatura; Problemas sociales en la literatura; LITERARY CRITICISM -- Poetry; LITERARY CRITICISM -- Semiotics & Theory; American poetry -- Mexican American authors; American poetry -- Mexican influences; Mexican Americans in literature; Mexican Americans -- Intellectual life; Social problems in literature; Criticism, interpretation, etc